KEBERAGAMAN MASYARAKAT DAN TOLERANSI BERAGAMA DALAM SEJARAH KERAJAAN SRIWIJAYA (SUATU ANALISIS HISTORIS DALAM BIDANG SOSIAL, BUDAYA, EKONOMI DAN AGAMA) - Sholeh, Kabib (Balai Arkeologi Sumatera Selatan, 2018)
The kingdom of Sriwijaya was known as the greatest protector and follower of Buddhismin the archipelago of his time. The diversity of society, race and religion make Sriwijayatruly able to maintain peace, diversity and tolerance among religious people.. The purposeof this study is to analyze the diversity of society in the kingdom of Sriwijaya in variousaspects of life, tolerance among religious communities between Buddhism, Islam andHinduism, and the factors emergence of life tolerance in the kingdom of Srivijaya. Themethod used is historical method. The steps in historical methods include heuristics (datacollection / source), verification (selection or source criticism), interpretation (historicalinterpretation) and the last is historiography (historical writing). This research explains thediversity of society in the Sriwijaya kingdom from indigenous peoples, Arabs, Indians andChinese, and the foreign community is in the kingdom of Sriwijaya due to economic factorsand they enter by trade. The diversity of the people in the kingdom of Sriwijaya is highlyprotected by the king of Sriwijaya kingdom so there is no emphasis, murder, threats fromthe king of Sriwijaya kingdom unless they do the rebellion will be burned. The king of thekingdom of Sriwijaya felt happy and respected the diversity of his people. The king of thekingdom of Sriwijaya is open to strangers, loving peace based on the unreliability ofleadership in accordance with his Buddhist teachings. Such conditions have an impact onthe policy of the king of Sriwijaya kingdom in addressing a difference in running beliefs andreligions such as Buddhism, Islam, Hinduism and local beliefs. Sriwijaya highly upholdsreligious tolerance as depicted on the Hindu temple site Bumiayu temple, the arrival andsettlement of Muslim traders in the kingdom of Sriwijaya, so that the kingdom of Sriwijayasent a letter to the Umayyads to request the sending of a mubaleq as king's adviser. All theseevidences depict the king of the kingdom of Sriwijaya very tolerant of other religions.